Modification of the pneumatic retinopexy for the treatment of rhegmatogenous retinal detachment with multiple-quadrant retinal breaks - Xin Zhang; Haixiu Wu; Shenchao Guo; Tiepei Zhu; Zhenyang Xiang; Gaochun Li; Enhui Li (Frontiers in Medicine)
PurposeThis study aimed to evaluate the efficacy of a modified pneumatic retinopexy (PR) procedure for patients with rhegmatogenous retinal detachment (RRD), particularly those with multiple-quadrant retinal breaks that spanning more than three clock-hours of retinal arc.MethodsThis prospective case series included ten eyes of ten patients, all of whom underwent the PR surgery during hospitalization. The modified PR technique involved an intravitreal injection of a low concentration of perfluoropropane (14% C3F8) for gas tamponade and head positioning maneuvers guided by an indicator. The multiple breaks were closed by gas bubble and treated with immediate laser photocoagulation one by one during the sequential alternating head positioning maneuver.ResultsAfter the modified PR surgery, retinal attachment was achieved in 9 of the 10 eyes (90%). The single case of failure, due to significant vitreous hemorrhage following gas injection, underwent a vitrectomy and received retinal attachment. Permanent retinal attachment was achieved in all cases (100%) at the last follow-up with no adverse events. The mean preoperative best-corrected visual acuity was improved significantly at 6 months post-surgery.ConclusionThis study demonstrates the potential of modified PR to achieve high success rates in RRD cases with multiple-quadrant retinal breaks cases involving superior retinal detachments and early proliferative vitreoretinopathy.